Look before you leap: the economics of free trade and income redistribution - Erich Gundlach; Albert de Vaal (Kiel Institute for the World Economy (IfW), 2010)
Economists tend to exalt the virtues of free international trade, while politicians are more skeptical. This paper suggests that this is the case because politicians mainly worry about the income distribution effects of trade liberalization, while economists focus on efficiency. Using textbook economic analyses we show that compensating the income distribution effects of free trade may be more complicated and hazardous than is often assumed, at least from a comparative static point of view. Hence politicians may favor trade liberalization only when distributional effects are ignored. By using a multitude of analytical tools and approaches, our paper also makes a useful teaching case for undergraduate students to test and gear their thinking about trade policy issues.
Keywords: A20; F13; H20; 330; Trade policy; income distribution; compensation schemes; undergraduate teaching